Development of Basic Chemistry Lab Work Module as Science Process Skills Assessment - Aisyiah Restutiningsih Putri Utami; Mustapa Mustapa; Chaleb Paul Maanari; Stefan Marco Rumengan; Jakub Saddam Akbar; Musma Rukmana (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Nahdlatul Wathan Mataram, 2025)
In this research, a lab work module daily life base has been successfully developed in the basic chemistry 1 lab work. This module was created to make practicum implementation easier in the chemistry laboratory due to limited tools and materials. This research aims to assess students' science process skills. The lab work module development process uses the ADDIE model research approach. After that, the validation tests carried out were media experts and material experts, each consisting of two experts, and average validation test scores for material and media experts were found to be 4.67 and 4.54, respectively. These results indicate that the module is suitable for use as a learning resource. The next step was to test its practicality and effectiveness using pretest and posttest instruments, students' score results, and questionnaires. Data analysis was carried out using descriptive statistical methods and the results obtained were that the module was suitable and practical for use as a learning resource with a practicality percentage of 89.47%. Furthermore, the student's learning completion results were 100% and the N-Gain value was 0.71, which proves that the module created is effective. In conclusion, the product that has been developed is successful in improving students' science process skills.